Gradiente social, envejecimiento y diagnóstico tardío del cáncer oral (2011)
ABSTRACT: A public health-based perspective is required to approach, with greater interest, both oral health problems and the identification of their main determinant factors. One of such problems is oral cancer. In this study, a narrative literature review was conducted while including some elements of critique and opinion. We highlight the fact that inequalities in oral health are yet to be completely understood, especially those related to oral cancer. The main characteristics of oral cancer are its accumulative nature and its prevalence in the elderly. In developing countries, this population is at social disadvantage, mainly because of the future demographic transition, the social gradient and a failure to detect the condition early. This review approaches these topics. Accordingly, it is very important to understand the causes of oral cancer‘s late diagnosis in terms of its social determinants in order to strengthen the public policies regarding cancer in general.